Find the inverse function of h(x) = - 2/3x + 6.

h -1(x) = -3/2x + 9
h -1(x) = -3/2x - 6
h -1(x) = -2/3x + 9
h -1(x) = -2/3x - 6

Answers

Answer 1
let y=h-1(x) and lastly, find y
Find The Inverse Function Of H(x) = - 2/3x + 6. H -1(x) = -3/2x + 9 H -1(x) = -3/2x - 6 H -1(x) = -2/3x

Related Questions

the diagonals of a rhombus are 12 centimeters and 16 centimeters. what is the length of one side of the rhombus?

Answers

in a rhombus, the diagonals meet at right-angles, and they bisect each other, namely they cut each other in half, check the picture below.

thus we can use the pythagorean theorem to get one side, keeping in mind that, slanted as it may be, all sides in a rhombus are equal in length.

The period T in seconds of a simple pendulum of length L in feet is given by T=2π√L/32. Determine the length in feet of a simple pendulum whose period is 8.72 seconds. Round your answer to the nearest foot.

1972 feet.
387 feet.
62 feet.
256 feet.

Answers

For this case we have the following equation:
 T = 2π√L / 32
 Clearing L we have:
 T / 2π = √L / 32
 (T / 2π) ^ 2 = L / 32
 L = 32 * (T / 2π) ^ 2
 Substituting values:
 L = 32 * (8.72 / (2 * (3.14))) ^ 2
 L = 61.69694511 feet
 Round to the nearest foot:
 L = 62 feet
 Answer:
 
L = 62 feet
 In this situation, you have to use the equation
T = 2π√L / 32
 We need to find L so we have:
 T / 2π = √L / 32
 (T / 2π) ^ 2 = L / 32
 L = 32 * (T / 2π) ^ 2

 Substitute the values:
 L = 32 * (8.72 / (2 * (3.14))) ^ 2
 L = 61.69694511 feet
 L = 62 feet
 So the Answer is
 L = 62 feet

Can someone please help me with this??

(PLEASE USE THE PICTURES ABOVE)

And please do what it says.

Thanks soo much


thanks

Answers

Asked and answered elsewhere.
https://brainly.com/question/9951374

how do I solve (x-5)(x-1)=0

Answers

With this equation, you'd distribute one set of parenthesis into the other. Doing so you'd get "X^2 - 1x - 5x + 5 = 0". Simplified, you'd have "X^2 - 6x + 5 = 0"

Next, you'd find the factors of 5, that when multiplied equal 5, and when added, equal -6. Being that 5 is a prime number (a number that is only divisible by 1 and itself) those numbers are 1 and 5. Both numbers have to be negative, in order to get -6.

-1*-5 = 5
-1 + -5 = -6

Finally you split up the X^2 to a single x with each of the factors and make it equal to zero (X - 1 = 0) and (X - 5 = 0). Then you solve each.

(X - 1 = 0) Add 1 to each side. X = 1
(X - 5 = 0) Add 5 to each side. X = 5

I hope this helps!

Alan is giving a basic math test in his class. One of the questions in the test is about finding two factors of the number 221. Which are the two factors of the given number? The two factors of the number 221 are ___ and ____.

Answers

1,13,17 are three of them 

The two factors of the number 221 are 13 and 17. 
A factor refers to a whole number, which fits evenly into another whole number. Thus, factors are the numbers, which we multiply together to get another number. The two numbers that can be multiply together to get 221 are 13 and 17.

What is the linear function that best fits the data set?

Answers

Answer: Fourth option y=-3x+15
Please, see the attached file.
Thanks.

What is the value of x? Round the answer to the nearest tenth. The diagram is not drawn to scale.

Answers

x = 50 

Reason: Chord AB and Chord CD are equal.

We have been given that the chords AB and CD are equal.

Now, we know that two equal chords subtends equal angle at the center of the circle.

The chord CD subtends and angle CPD at the center and the chord AB subtends an angle APB at the center.

Hence, from above mentioned theorem, we can say that

[tex]\angle CPD = \angle APB[/tex]

Now, we have been given that

[tex]\angle CPD =50 ^{\circ} [/tex]

[tex]\angle APB =x ^{\circ} [/tex]

Hence, we have

[tex]x=50^{\circ}[/tex]

someone help me please

Answers

For this case we have the following functions:
 f (x) = 3x + 1
 g (x) = x ^ 2 - 6
 Subtracting both functions we have:
 (f-g) (x) = f (x) - g (x)
 (f-g) (x) = (3x + 1) - (x ^ 2 - 6)
 (f-g) (x) = 3x + 1 - x ^ 2 + 6
 (f-g) (x) = - x ^ 2 + 3x + 7
 Answer:
 
(f-g) (x) = - x ^ 2 + 3x + 7
 option B

PLEASE HELP 50 point will give brainlyest
Evaluate 81000−−−−√3 .


1/125

6/500

8/500

2/10

Answers

when I did it I got 140296.11541307
THE ANSWER IS B: 6/500 :) JUST LIKE IT AND VOTE ON IT PLZ THANK U AND HAVE A OOF DAY XD have a good day lel

How do you use properties of exponents and logarithms to rewrite functions in equivalent forms and solve equations?

Answers

Some of the logarithmic properties most used to solve equations are the following.
 1) log (a) ^ b = b * log (a)
 2) log (a * b) = log (a) + log (b)
 3) log (a / b) = log (a) - log (b)
 These logarithmic properties can be used to solve equations.
 For example:
 2 ^ x = 56
 If we apply to this equation the logarithm function on both sides that we have left
 log (2) ^ x = log (56)
 This function is equivalent to the first.
 If we now apply the property 1) of the previous logarithms, we can reveal x of the equation.
 x * log (2) = log (56)
 x = log (56) / log (2)
 x = 5,807
 Thus, thanks to the properties of the logarithms, this exponential function could be solved

Final answer:

To use properties of exponents and logarithms effectively, one must apply specific rules such as the logarithm of a product being the sum of the logarithms and the logarithm of a number raised to an exponent being the product of the exponent and the logarithm. Log transformations help linearize and solve equations involving exponents.

Explanation:

To rewrite functions in equivalent forms and solve equations using the properties of exponents and logarithms, one must understand several key rules and relationships. For example, the common logarithm (log) indicates the power to which 10 must be raised to equal a given number.

Two essential properties we use are:

The logarithm of a product of two numbers is the sum of the logarithms of the two numbers (log xy = log x + log y).The logarithm of a number raised to an exponent is the product of the exponent and the logarithm of the number (log x^n = n log x).

Exponential and logarithmic functions are inverses. This relationship allows us to simplify complex expressions and solve exponential equations by taking the logarithm of both sides. For instance, the natural logarithm (ln or loge) and the base e exponential are inverse functions, so ln (e^x) = x and e^(ln x) = x.

A log transformation can linearize functions that involve an exponent by taking the log of both sides of the equation. This technique is valuable in solving equations where the variable is an exponent.

Kenny is making creamy rice pudding his recipe requires 4 cups of milk he has a quart of milk in his fridge dose he have enough milk explain

Answers

yes, because 4 cups = 1 quart 

3.2km/50min X 60min/1hr X 1mi/1.6km

A) 2.4mi/hr
B) 2.4km/hr
C) 12mi/hr
D) 12km/hr

Answers

3.2km    60min       1mi                          km            min
-------- x --------  x ----------- (cancel out:  ---- and   ------   )
50min     1hr         1.6km                       km            min


   2.4 mi     
= ---------
    hr     

answer
A) 2.4mi/hr
Final answer:

The student's conversion calculation of speed units from kilometers per minute to miles per hour yields a speed of 2.4 miles/hour, so the answer is choice A.

Explanation:

The question is a conversion exercise in speed units from kilometers per minute to miles per hour. We have the following information: 3.2 km in 50 min, and we know that 1 mile is equivalent to 1.6 km and 60 min is equivalent to 1 hour. Thus, the conversion is as follows:

3.2 km ÷ 50 min. = 0.064 km/min.

Converting km/min to mi/hr involves multiplying by 60 (minutes in an hour) and dividing by 1.6 (km in a mile), and we get:

(0.064 km/min x 60 min/hr) ÷ 1.6 km/mi. = 2.4 mi/hr.

Hence, the correct answer is (A) 2.4 miles/hour.

Learn more about Conversion Exercise here:

https://brainly.com/question/32748122

#SPJ2

on Sunday Mary pay $6 each on two tickets to a movie theater movies for $9.58 each Mary paid with 3 $20 bills how much changed

Answers

$50.42







hjdjdjdjdbdhshssjdjdjdjdj

Plato explains that we know geometry by _________.

Answers

Plato explains that we know geometry by our gain knowledge through recollection. Our soul is what recollects this place hence we came where there exist unchanging truths. Delivered the theory of Forms, according to which the world people know by means of the senses is just an imitation of the eternal, pure, eternal, and fixed world of the Forms.

The Venn diagram represents the results of a survey that asked participants whether they would want a bird or a fish as a pet.



Enter your answers in the boxes to complete the two-way table based on the given data.

Answers

Answer with Step-by-step explanation:

As we can see the venn diagram:

number of bird+fish=6

number of bird+not fish=8

number of fish+not bird=19

and number of not fish and not bird=22

Hence, we get the following table

                        Fish           Not Fish            Total

Bird                6                    8                       14

Not Bird         19                  22                       41

Total               25                 30                       55

                Fish    Not Fish   Total

Bird            6            18           14

Not Bird    19           22          41

Total          25           30         55

suppose you drop a tennis ball from a height of 15 feet. After the ball hits the floor, it rebounds to 85% of its previous height. how high will the ball rebound after its third bounce? round to the nearest tenth

Answers

The answer would be 10.84

The diameter of a bowling ball is 12.57 centimeters. What is this value rounded to the nearest tenth of a centimeter?

Answers

For this case we have the following numerical value:
 12.57 centimeters
 We note that the number is rounded to the nearest hundredth.
 If we want to round the number to the nearest decimal we must rewrite the number.
 Rewriting we have:
 12.6 centimeters
 Answer:
 
this value rounded to the nearest tenth of a centimeter is:
 
12.6 centimeters
12.6 cm is the correct answer.

Solve the quadratic equation. 8x2 + 16x + 8 = 0 A) 1 B) -1 C) 1 and 8 D) 1 and -1

Answers

[tex]8x^2+16x+8=0\\\\8(x^2+2x+1)=0\ \ \ |:8\\\\x^2+2x+1=0\\\\x^2+x+x+1=0\\\\x(x+1)+1(x+1)=0\\\\(x+1)(x+1)=0\\\\(x+1)^2=0\iff x+1=0\\\\\boxed{x=-1}[/tex]
Answer: B. -1

Haley read three less than twice as many books as her brother did last summer. haley read five books.which equation could you use to find how many books her brother read (b)?

Answers

Your answer would be 2b-3=5
The 2 stands for the "twice as many"
The b stands for her brother.
The 3 stands for the "3 less books"
And the 5 stands for Haley's total.

I hope this helps!

Answer:

2b - 3 = 5

Step-by-step explanation:

If her brother read b number of books last summer, twice the number of books her brother read

= 2b

three less than twice as many books as her brother read

= 2b - 3

If haley read five books and it is same as three less than twice as many books as her brother last summer, then

2b - 3 = 5

A catapult is malfunctioning and not throwing objects in the intended manner. The builders have modeled the path of the objects thrown by using the following parametric equations. rewrite the parametric equations by eliminating the parameter.
x(t)=2t-1
y(t)= square root of t; t> or equal to 0

Answers

Answer:

The equation is [tex]y ^ 2 = \frac{x + 1}{2}[/tex]

Step-by-step explanation:

The parameter that we have is t. We want to eliminate this parameter in both equations, therefore in the first equation we solve for t and in the second equation we solve for the variable t.

We have:

[tex]x = 2t-1\\\\x + 1 = 2t\\\\t = \frac{x + 1}{2}[/tex]

Now we solve the other equation for t.

[tex]y= \sqrt{t}[/tex]

[tex]y ^ 2 = t[/tex]     because   [tex]t> 0[/tex]

As [tex]t = y ^ 2[/tex] and also [tex]t = \frac{x + 1}{2}[/tex]

Then:

[tex]y ^ 2 = \frac{x + 1}{2}[/tex]

The correct answer is:

D. [tex]x=2y^{2} -1, y\geq 0[/tex]

I need help on this show steps pleaseeee!!!

Answers

Step #1 - convert 1 ⅓ into a mixed number,

[tex] \frac{1}{2}r - \frac{1}{3} - \frac{4}{3} = - \frac{7}{3} [/tex]

Step #2 - calculate the sum or difference of - ⅓ by -4/3,

[tex] \frac{1}{2}r - \frac{5}{3} = - \frac{7}{3} [/tex]

Step #3 - Multiply both sides by 6,

[tex] \frac{1}{2} (6)r - \frac{5}{3} (6) = - \frac{7}{3} (6)[/tex]

[tex]3r - 10 = - 14[/tex]

Step #4 - Move constant ( - 10 ) to the right and change its sign,

[tex]3r = - 14 + 10[/tex]

Step #5 - Calculate the sum

[tex]3r = - 4[/tex]

Step #6 - Divide both sides by 3 so we can isolate the variable r,

[tex]r = - \frac{4}{3} [/tex]

~~

I hope that helps you out!!

Any more questions, please feel free to ask me and I will gladly help you out!!

~Zoey

HELP!!!!!!NEED TO PASS!!!!WILL GIVE THE BRAIN!!!!!!!!!!!

Answers

Shifting left means adding a number to x.

So, x³ shifted 5 units to left will be (x + 5)³

Shifting 4 units upwards means adding 4 to the function value,

So, previous function shifted 4 units up will be (x + 5)³ + 4

Thus, g(x) = (x + 5)³ + 4

So, option b gives the correct answer



So, option b gives the correct answer

-2x+3 > x +24

Show steps how you got your solution

Answers

- 2x + 3 > x + 24

First we must get all variables on the same side and constants on the opposite side. To do so we subtract x from the right and the left. Then subtract 3 from both sides as well. 

- 2x - x > 24 - 3 

Now we combine like terms:

- 3x > 21

We must isolate the variable x. In order to do so, we divide both sides by - 3. When you divide by a negative number, you must also flip the inequality so the greater than becomes a less than. 

x < 21 / - 3

x < - 7 is your answer. 
Hello!

You can solve this algebraically

-2x + 3 > x + 24

Subtract x from both sides

-3x + 3 > 24

Subtract 3 from both sides

-3x > 21

Divide both sides by -3

Since you divided by a negative you flip the sign

x < -7

The answer is x < -7 or any number that is greater than -7

Hope this helps!

Help Geometry!!
AC is tangent to circle O at A. If , m<BY= 24 , what is m<YAC?

a) 48

b) 156

c) 78

d) 132

Answers

we know that
The inscribed angle measures half of the arc it comprises.
so
∡BAY=BY/2------> 24/2------> 12°

angles YAC and BAY are complementary angles
∡YAC+∡BAY=90°
∡YAC=90-∡BAY-------> ∡YAC=90-12-----> 78°

the answer is
78°

To solve this system of equations by elimination, what operation could be used to eliminate the y-variable and find the value of x? 2x − 4y = 6 −3x + 3y = 12 A) add 3 times the second equation to 4 times the first equation B) add 4 times the second equation to 3 times the first equation C) subtract 3 times the second equation from 4 times the first equation D) subtract 4 times the second equation from 3 times the first equation

Answers

Answer:

Option B is correct.

add 4 times the second equation to 3 times the first equation

Step-by-step explanation:

Given the system of equation:

[tex]2x - 4y = 6[/tex]                         ......[1]

[tex]-3x + 3y =12[/tex]                       .....[2]

Multiply equation [1] by 3 we get;

[tex]3(2x-4y) = 3 \cdot 6[/tex]

Using distributive property; [tex]a\cdot (b+c) = a\cdot b+ a\cdot c[/tex]

6x - 12y = 18                                   .......[3]

Multiply equation [2] by 4 we get;

[tex]4(-3x+3y) = 4 \cdot 12[/tex]

Using distributive property we get;

-12x + 12y = 48                                   ......[4]

Add equation [3] and [4] to eliminate y and solve for x;

(6x -12y) + ( -12x +12y ) = 18 + 48

6x - 12y -12x + 12y = 66

Combine like terms;

6x - 12x = 66

or

-6x = 66

Simplify:

x = -11

Therefore, the operation which could be used to eliminate the y-variable and find the value of x is;

add 4 times the second equation to 3 times the first equation.

Answer:

Option B

Step-by-step explanation:

Given is a system of two equations as

[tex]2x − 4y = 6 \\−3x + 3y = 12[/tex]

To solve them using elimination:

Elimination method is the method of making coefficients of one variable numerically equal

IN the given system we have -4 as coefficient for y in I equation and 3 for y in II equation.

To make them numerically equal with opposite signs we can multiply I equation by 3 and II by 4

WE get

[tex]6x-12y =18\\-12x+12y=48[/tex]

Now if we add these two we are able to eliminate y from the system

Adding gives

[tex]-6x=66\\x=-11[/tex]

So option B is right

Need help on this question

Answers

Total Area: T.A.=2*Ab+Al

Area of the base: Ab=p*K

Semi-perimeter of the base: p
p=P/2
Perimeter of the base: P=20
p=P/2=20/2→p=10
Ab=p*k=10*K→Ab=10K

Lateral Area of the prism: Al
Al=P*h
Height of the prism: h=6
Al=P*h=20*6→
Al=120

T.A.=2*Ab+Al
T.A.=2*(10K)+120
T.A.=20K+120
T.A.=120+20K

Answer: (120+20K)



How to find the volume of a equilateral triangular prism?

Answers

The formula for a prism is the area of the base multiplied by the height. To find the area of the base of a triangular prism you would use the formula for the area of a triangle which is 1/2 base*height and then you would multiply that number by the height of the prism and your answer would need to be in cubic units.

Which triangles are similar?

a
b
c
d

Answers

i think A. and D.

hope that's right!!!
Hey there!

The two triangles that are similar are triangles A and D.

I hope this helped! :-)

Find the value of the combination 9 c 4

Answers

9C4= 126.

Hope this helps

please help- Your supposed to find x, y, and z and round to the nearest tenth

Answers

Didn't you mean "you are" or "you're?"

You didn't indicate which problem you wanted your helper to focus on.  So I will arbitrarily choose #2.

This large triangle is made up of two smaller triangles:  the smaller triangle has sides of 2 and x and hypotenuse of y.  The larger triangle has sides x and 5 and hypotenuse z.  Look carefully:  The largest triangle has hypotenuse (2+5) and sides y and z.  Now you have three equations in three unknowns and thus have enough info to find the values of x, y and z.

Think about this.  What should you do first?  Type back your ideas.  Then I'll help you solve this problem.

Other Questions
If two individuals that are heterozygous for the sickle cell allele (aa) mate with one another, what is the chance that their child will have sickle cell anemia ? Can someone help me in this trig question, please? thanks A person is on the outer edge of a carousel with a radius of 20 feet that is rotating counterclockwise around a point that is centered at the origin. What is the exact value of the position of the rider after the carousel rotates 5pi/12 Eight times the sum of a number and one is -8 bursectomy medical terminology A student drew the following flowchart. Crushing Sizing Concentrating Dewatering What is the purpose of the process? Which process is a feature of webmail? A.)allows user collaboration when creating content B.)downloads messages to the clients machine C.)helps to conduct meetings in real time D.)runs from a server economic interdependence definition Kordell is interested in distributing questionnaires to college freshmen regarding their study habits. he has targeted several colleges where he wants to carry out the research. what must kordell do first? This map shows the Western expansion of the United States.Describe events that explain the border differences between these maps. Use information from the maps and the lesson in your response. Use complete sentences.Besides land, what did the United States gain from expansion? Use information from the maps and the lesson in your response. Use complete sentences. sketch one cycle of the cosine function y=-cos 3 theta use the graph of f(x)to find the solutions to the equation f(x)=0. The rarity and cost in obtaining fresh lobster makes it a delicious __________. A. delicacy B. occasion C. decoration D. investment Questions 18-20 refer to the reaction 2NH3 (g) N2 (g) + 3H2 (g), and H = 92.2 kJ. What will be the effect on the concentration of H2 if the temperature decreases?A. H2 concentration will decrease.B. H2 concentration will not change. C. H2 concentration will increase. D. H2 concentration will not change, but H will decreaseE. H2 concentration will not change, but pressure will increase.What will be the effect on the concentration of NH3 if the pressure decreases?A. NH3 concentration will decrease.B. NH3 concentration will not change.C. NH3 concentration will increase.D. NH3 concentration will not change, but H will decrease.E. NH3 concentration will not change, but entropy will increase. What will be the effect on N2 if the concentration of NH3 increases? _______A. N2 concentration will decrease.B. N2 concentration will not change.C. N2 concentration will increase.D. N2 concentration will not change, but H will decrease.E. N2 concentration will not change, but pressure will increase. How to build a positive relationships Astronomers these days can do the most amazing things. If someone struck a match on the Moon, they could spot the flare. From the tiniest throbs and wobbles of distant stars they can infer the size and character and even potential habitability of planets much too remote to be seenplanets so distant that it would take us half a million years in a spaceship to get there. With their radio telescopes they can capture wisps of radiation so preposterously faint that the total amount of energy collected from outside the solar system by all of them together since collecting began (in 1951) is less than the energy of a single snowflake striking the ground, in the words of Carl Sagan. Source: Bryson, Bill. Welcome to the Solar System. A Short History of Nearly Everything. New York: Broadway, 2003. 19. Print. What is the authors main purpose in this excerpt? why did early slav communities develop in the are of western russia The second Klan had faded from power by the start of __________. A. World War I B.the Roaring 20s C. the Great Depression D. World War II Subtract.(x + 1) (2x 5) turn 0.43,0.50 into a median 20 points The next step in the solution for which equation could use the distributive property? A. 4(t-6)=3t+9B. 4(t6)=3t+9C. 4t-6+3t=9D. 4t1/4=3t+9